Pengetahuan Konseling Sebaya Untuk Menumbuhkan Motivasi Pencegahan Penyalahgunaan Narkoba Pada Siswa - Karjuniwati, Karjuniwati; Nova, Vera; Kamal, Ahmad Maulana; Zuanny, Iyulen Pebry; Bintang, Siti Syapiah (UIR Press, 2023)
Drug abuse is increasingly common among teenagers due to environmental influences. Peer influence plays a role in providing counseling to help students avoid drug abuse. The study aimed to describe the influence of peer counseling knowledge to grow motivation to prevent drug abuse in students. The measuring instruments for this research used a peer counseling knowledge questionnaire and a drug abuse prevention motivation questionnaire. The sampling technique used was purposive sampling with a sample size of 30 students. The data analysis technique used is simple linear regression with a significance value of 0.005 <0.05, which means that there is a very significant influence of Peer Counseling Knowledge on Motivation to Prevent Drug Abuse in students. In the R Square (R) test, an R Square value of 0.251 (25.1%) was obtained. This shows that the peer counseling knowledge variable influences the motivation to prevent drug abuse by 25.1%. Meanwhile, 74.9% were influenced by other factors.